The feminist ideas of Nawal El Saadawi in light of the intellectual foundations of existencialism and socialism // Las ideas feministas de Nawal El Saadawi a la luz de los fundamentos intelectuales del existencialismo y el socialismo - Giti, Shahriar; Yusefi, Fatemeh (Interacción y Perspectiva, 2019)
Abstract The Feminist critique, by revising some of its notions, and attempting to understand the cruel nature of what seemed like an autonomous philosophy, was based on stereotypes imposed by the society on women (stereotypes such as the woman of death, The angel in house and the moral guard of man), and these representations are linked to the humiliation of women in social life. Consequently, throughout its history, it has been continually calling for the abolition and destruction of the patriarchal system and the elimination of the predominance of gender discrimination. This movement has several peculiarities, of which the most important are existentialist feminism and socialist feminism. Nawal Sadawi is one of the feminist writers in the Arab world; in her works, including the novel "a Woman at zero point ", she deals with the patriarchal system and gender discrimination stemming from social and religious traditions. In this essay, we have examined the feminist ideas of Nawal El Saadawi in light of her being influenced by intellectual foundations of existentialism and socialism in the novel “Woman at zero point ". To Nawal El Sadawi the suppression of women is the fundamental form of patriarchy. Hence, she often defines male dependency in terms of male sexual feelings. Resumen La crítica feminista, al revisar algunas de sus nociones e intentar comprender la naturaleza cruel de lo que parecía una filosofía independiente, se basó en los estereotipos impuestos por la sociedad a las mujeres (estereotipos como la mujer de la muerte, El ángel en casa y la guardia moral del hombre), y estas representaciones están vinculadas a la humillación de las mujeres en la vida social. En consecuencia, a lo largo de su historia, ha reclamado continuamente la abolición y destrucción del sistema patriarcal y la eliminación del predominio de la discriminación de género. Este movimiento tiene varias peculiaridades, de las cuales las más importantes son el feminismo existencialista y el feminismo socialista. Nawal Saadawi es una de las escritoras feministas en el mundo árabe; en sus obras, incluida la novela "La mujer en el punto cero", trata sobre el sistema patriarcal y la discriminación de género derivada de las tradiciones sociales y religiosas. En este ensayo, hemos examinado las ideas feministas de Nawal El Saadawi a la luz de su influencia en los fundamentos intelectuales del existencialismo y el socialismo en la novela "La mujer en el punto cero". Para Nawal El Saadawi, la supresión de las mujeres es la forma fundamental del patriarcado. Por lo tanto, a menudo define la dependencia masculina en términos de sentimientos sexuales masculinos.